If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 8 * 0 = 40 Multiply 8 * 0 -1x + 0 = 40 Anything times zero is zero. -1x + 0 = 40 Reorder the terms: 0 + -1x = 40 Remove the zero: -1x = 40 Solving -1x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = -40 Simplifying x = -40
| 15x-15-4x+8=-2x-4 | | -0+8y=40 | | 15x-15-4x+8=-2x-2 | | 9x-4*0=54 | | 9*0-4y=54 | | 6x(2/3) | | -13x-0=39 | | -13*0-y=39 | | 2p+5=-9 | | 3x-12+5=2x+13 | | 10z+2=5 | | 5p+pq+6pr= | | Y=2X-40 | | -x-5*0=12 | | 36x+5(9x-x)-3x= | | 2X-40=1Y | | -0-5x=12 | | (2X-40)=Y | | 5x-91=-11 | | Logx=18.8 | | 7x-12x-5=-42+15 | | ((1/5)x^(-1/5))*(4-9x)=0 | | 0.072=1-z | | 7+-2+-4= | | 8=3.14+x | | y-21/7=x | | -8x+3(x-2)=11 | | 17=2x+6 | | 15-4x-3x^2=0 | | 2y^2+17y+31=(y+5)(y+5) | | x^2+5x+6=-x^2-3x | | -7/5y-7/2=7y-4/5 |